2015
DOI: 10.9775/kvfd.2014.12722
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’deki Beş Yerli Sığır Irkında Et Verim Özellikleri ile İlişkili Beş Genin Polimorfizmi

Abstract: There are many potential genes that are known to be related to meat production and that can be used for selection to improve meat quality and production include Calpain (CAPN1), Myostatin (MSTN), Calpastatin (CAST), Osteopontin (SPP1) and Thyroglobulin (TG). This study evaluated Zavot (n=60), Anatolian Black (n=59; AB), South Anatolian Red (n=53; SAR), Turkish Gray (n=60; TG) and East Anatolian Red (n=49; EAR) cattle breeds, with the primary goal of investigating DNA polymorphisms of the CAST, TG, SPP1, MSTN a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
3
2
Order By: Relevance
“…The C allele frequency in our sample which is made up of purebred TGC is 0.559, which is also lower than the frequencies reported by previous researchers [20,21] . For the UoG-CAST SNP genotypes Gill et al [22] found the CC, CG and GG genotypic frequencies in Aberdeen Angus cattle as 0.41, 0.47 and 0.12, respectively.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…The C allele frequency in our sample which is made up of purebred TGC is 0.559, which is also lower than the frequencies reported by previous researchers [20,21] . For the UoG-CAST SNP genotypes Gill et al [22] found the CC, CG and GG genotypic frequencies in Aberdeen Angus cattle as 0.41, 0.47 and 0.12, respectively.…”
Section: Discussioncontrasting
confidence: 76%
“…On the other hand, Schenkel et al [5] found them as 0.430, 0.398 and 0.172, respectively for Bos taurus while Curi et al [11] found 0.377, 0.491 and 0.132, respectively for purebred Bos indicus Nellores. In our study, the ratio of the purebred TGC with CC genotype which expected to beef with more tenderness is lower than previous researches [20,21] , except Kök et al [23] . The CAPN1 316 C allele is associated with meat tenderness.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…However, it has been reported that the allelic frequencies of the native breeds are lower than those of pure blood European breeds [38] . Correct usage of crossbreeding and artificial insemination techniques on native breeds in order to increase the allelic frequencies will be beneficial on the amelioration of milk quality parameters which in turn make it possible to provide the consumer with higher quality milk [39] . For example, cattle carrying the allele A of the gene ABCG2 (which codes the Breast Cancer Resistant Protein, Bcrp) have been reported to be selected since they are economically favourable [40] .…”
Section: Discussionmentioning
confidence: 99%